2006
DOI: 10.1038/sj.ki.5000277
|View full text |Cite
|
Sign up to set email alerts
|

Conditionally immortalized human glomerular endothelial cells expressing fenestrations in response to VEGF

Abstract: Glomerular endothelial cells (GEnC) are specialized cells with important roles in physiological filtration and glomerular disease. Despite their unique features, GEnC have been little studied because of difficulty in maintaining them in cell culture. We have addressed this problem by generation of conditionally immortalized (ci) human GEnC using technology with which we have previously produced ci podocytes. Primary culture GEnC were transduced with temperature-sensitive simian virus 40 large tumour antigen an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
199
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 198 publications
(211 citation statements)
references
References 29 publications
11
199
0
1
Order By: Relevance
“…We have previously shown that ibidi systems are able to orient semi-rigid molecular systems [24]. Human conditionally immortalized glomerular endothelial cells (GEnCs) [25] were grown as described in the ESM. The completed M13 construct was bound to the flow slide coating (collagen IV or endothelial cells) and any unbound M13 was rinsed off.…”
Section: Methodsmentioning
confidence: 99%
“…We have previously shown that ibidi systems are able to orient semi-rigid molecular systems [24]. Human conditionally immortalized glomerular endothelial cells (GEnCs) [25] were grown as described in the ESM. The completed M13 construct was bound to the flow slide coating (collagen IV or endothelial cells) and any unbound M13 was rinsed off.…”
Section: Methodsmentioning
confidence: 99%
“…Conditionally immortalised human glomerular endothelial cells were also used. The characteristics of these cells have been reported elsewhere [22]. In addition, murine 3T3-L1 fibroblast clones were obtained from LGC Promochem (Teddington, UK).…”
Section: Methodsmentioning
confidence: 99%
“…Primary endothelial cells maintained in culture have a shortened life-span and require supplementation of growth media with cytokines and serum that result in the loss of their unique endothelial cell features (6). Different methods were previously used to transform endothelial cells to increase their life-span including transformation with human telomerase (17,18), polyoma middle T antigen (19), SV40 large T antigen, adenoviral E4 genes (10) or combination of transforming agents (8).…”
Section: Mass-spectroscopy Analysis Of 293-e4mentioning
confidence: 99%
“…Thus the limited life span and dependence on serum and growth factors put a considerable limitation to studies that can be conducted with primary endothelial cells. Human primary glomerulus-derived endothelial cells (PrGECs) either transformed with a simian virus 40 (SV40) (7) or conditionally immortalized with temperature-sensitive SV40 large T antigen and telomerase using retroviral vectors (8) retain the ability to grow up to 60 passages and maintain endothelial cell markers. However, culturing these transformed or immortalized cell lines still requires supplementation with serum and growth factors and their withdrawal leads to quick cell death (9).…”
mentioning
confidence: 99%